2016
DOI: 10.1111/trf.13882
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial to evaluate the use of text messaging, letter, and telephone call reminders to improve return of blood donors with reactive serologic tests

Abstract: Introduction Low return rates for notification and counseling among donors with reactive serologic screening tests have been reported worldwide. A randomized trial to test the effectiveness of text message, letter or telephone call reminders to improve return among non-responding first-time blood donors with reactive serologic tests was conducted. Methods Donors with serologically reactive screening test results who had a cell phone and resided in the metropolitan telephone area code of São Paulo in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
2
9
0
5
Order By: Relevance
“…Fourth, our findings underscore the potential benefits of effective communication with blood donors about making and keeping donation appointments. Indeed, we found that gains in blood collection achieved through comprehensive reminders were similar to those obtained by reducing inter-donation intervals 36 , 37 (although part of this gain is likely to have been due to the effects of participating in a research study 38 ). Finally, as this trial has identified subsets of donors with readily measured characteristics (eg, those with higher than average ferritin concentrations) who have greater capacity than other donors to give blood more frequently, our study contributes to the possibility of increased personalisation of blood donation.…”
Section: Discussionmentioning
confidence: 54%
“…Fourth, our findings underscore the potential benefits of effective communication with blood donors about making and keeping donation appointments. Indeed, we found that gains in blood collection achieved through comprehensive reminders were similar to those obtained by reducing inter-donation intervals 36 , 37 (although part of this gain is likely to have been due to the effects of participating in a research study 38 ). Finally, as this trial has identified subsets of donors with readily measured characteristics (eg, those with higher than average ferritin concentrations) who have greater capacity than other donors to give blood more frequently, our study contributes to the possibility of increased personalisation of blood donation.…”
Section: Discussionmentioning
confidence: 54%
“…One study reported most of their control group used their own reminder, potentially confounding the non-significant outcomes ( Hou et al, 2010 ), and a second study hypothesized that many participants in the control group used their own reminder (although this was not formally assessed) ( Mbuagbaw et al, 2012 ). Another study found that a phone call reminder was more effective than a SMS reminder at increasing treatment follow-up appointment completion ( Porto-Ferreira et al, 2017 ). Two studies found both the treatment and control group had a significantly higher medication adherence and appointment attendance rate than typical ( Burton et al, 2014 ; Goldstein et al, 2014 ); and another hypothesized that due to the length of their study, the novelty and benefit of a medication reminder may have worn off ( Ting et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…It would be useful to extend the economic analysis undertaken here to examine whether or not the more intensive reminder system undertaken as part of the original INTERVAL trial was in itself cost-effective. 56,57 A strength of the CEA is that it used data from a large, well-conducted RCT with complete follow-up data for the main end points of interest, and included as a control arm the current minimum donation interval in England. The large sample size meant that it was possible to report both the overall effect of alternative minimum donation intervals (on frequency of attendance to donate whole blood and deferrals) and the effect according to subgroups of key policy relevance.…”
Section: Discussionmentioning
confidence: 99%